Processes of forming of aluminum nitride in plasma by action of defocuseddoble laser beams upon aluminum in airatmosphere - Bazzal, Khoder; Lychkowski, Vyicheslav V.; Zajogin, Anatoli P. (Journal of the Belarusian State University. Physics, 2019)
In order to determine optimal conditions of influence of defocusing of emission of double laser impulses aimed on forming required both component and charge composition of surface laser plasma a researches using laser spark spectrometry method were conducted. Processes of forming aluminum nitride by action of single and double defocused laser impulses on D16T in air atmosphere were studied. Role of first impulse on possibility of increase percentage both of aluminum ions of different charges in surface plasma during surface ablation mode of aluminum alloys by defocused double laser impulses, and nanoclusters of AlN by consistent action of series of double impulses on sample were shown. Conditions of influence of laser parameters and processes on sample surface and in plasma itself on forming of certain ion and molecule composition of plasma during action of single and double impulses.
Keywords: AlN; pulsed laser deposition; surface laser plasma; laser spark spectrometry; multiply charged ions; double laser pulses